1974
DOI: 10.1002/cjce.5450520105
|View full text |Cite
|
Sign up to set email alerts
|

Vertical two‐phase flow part I. Flow pattern correlations

Abstract: Two‐phase gas‐liquid flow has been investigated in a 1‐inch internal diameter vertical tube coil containing two risers and a downcomer all connected by “U” bends. Flow pattern data were obtained in the three vertical tubes, each 17.30 ft. long, for five different air‐liquid systems at about 25 psia over flow ranges of 0–700 lbm air/min‐ft2 and 140–25300 lbm liquid/min‐ft2. Liquid phase viscosities ranged from 1 to 12 cp. A flow pattern classification with six regimes including coring‐bubble, bubbly‐slug, falli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
4

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(72 citation statements)
references
References 21 publications
2
66
0
4
Order By: Relevance
“…These approaches attempt to account for the effect of factors such as fluid density, viscosity, surface tension, and pipe geometry within their proposed flow map systems [15][16][17][18][19][20][21][22].…”
Section: Figure 1: Illustration Of the Four Main Flow Regimes That Camentioning
confidence: 99%
“…These approaches attempt to account for the effect of factors such as fluid density, viscosity, surface tension, and pipe geometry within their proposed flow map systems [15][16][17][18][19][20][21][22].…”
Section: Figure 1: Illustration Of the Four Main Flow Regimes That Camentioning
confidence: 99%
“…The void fraction and the system temperature are chosen to be α=0.016 and T=298.2 K, respectively, throughout this study. Under such a low void fraction, the flow regime of the methane-water mixture is considered to be bubbly in the entire domain of the current flow loop (Mandhane et al, 1974;Oshinowo and Charles, 1974;Taitel et al, 1980), except for the pump flow at high pressure in which a transition from bubbly to jetting may be possible. More detail about the pump flow regime is addressed in Section 3.4.…”
Section: Test Ow Set Upmentioning
confidence: 99%
“…Abdulkadir et al (2012) concluded that the average film fraction is higher in straight pipes than in bends. And that the condition for which the liquid goes to the outside or inside of the bend can be identified based on a modified form of Froude number, a proposal first made by Oshinowo and Charles (1974). It is worth mentioning that the averaging effect of the conductance rings can result in differences in the time-varying data, as some details of the asymmetric nature of the liquid film thickness profiles can be affected.…”
Section: Two-phase Film Thickness Distribution In 180 O Bendsmentioning
confidence: 99%